Determinants of Johns’ Decision Making: An analysis of a Sex Tourism Web Forum - Lee, Julak (Advances in Social Sciences Research Journal, 2018)
Prostitution is one of the oldest professions in human society and the ways sex services are advertised and sought after have changed in recent decades. Specifically, with the emergence of cyberspace which allows for anonymity and secrecy, clients of sex workers, johns, are shown to exchange information in online forums. This method of information sharing is a common practice for those that buy sex in foreign countries, which help them through their decision-making process. In this study, posts in an online forum for the foreign johns in South Korea are examined in order to explore the important factors affecting their decision making.